2018
DOI: 10.1038/s41438-018-0108-0
|View full text |Cite|
|
Sign up to set email alerts
|

The chromosome-level quality genome provides insights into the evolution of the biosynthesis genes for aroma compounds of Osmanthus fragrans

Abstract: Sweet osmanthus (Osmanthus fragrans) is a very popular ornamental tree species throughout Southeast Asia and USA particularly for its extremely fragrant aroma. We constructed a chromosome-level reference genome of O. fragrans to assist in studies of the evolution, genetic diversity, and molecular mechanism of aroma development. A total of over 118 Gb of polished reads was produced from HiSeq (45.1 Gb) and PacBio Sequel (73.35 Gb), giving 100× depth coverage for long reads. The combination of Illumina-short rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
116
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(119 citation statements)
references
References 56 publications
2
116
1
Order By: Relevance
“…BUSCO assessment revealed that 90.0% of the complete BUSCOs could be found in the current assembled A. setaceus genome. This percentage was lower than those in Osmanthus fragrans (96.1%) 24 and Brassica oleracea (96.77%) 25 , but higher than those in the genomes of some other species, such as Ginkgo biloba (73.95%) 26 and A. officinalis (88.2%) 11 . Considering the high level of heterozygosity and repetitiveness of the genome, the current version represents a high-quality genome assembly of A. setaceus.…”
Section: Discussionmentioning
confidence: 63%
“…BUSCO assessment revealed that 90.0% of the complete BUSCOs could be found in the current assembled A. setaceus genome. This percentage was lower than those in Osmanthus fragrans (96.1%) 24 and Brassica oleracea (96.77%) 25 , but higher than those in the genomes of some other species, such as Ginkgo biloba (73.95%) 26 and A. officinalis (88.2%) 11 . Considering the high level of heterozygosity and repetitiveness of the genome, the current version represents a high-quality genome assembly of A. setaceus.…”
Section: Discussionmentioning
confidence: 63%
“…In this study, four tissue types from sweet osmanthus ('RiXiangGui'), including roots, stems, leaves (young and mature), and flowers in initial, full, and final flowering stages, were collected. Fresh flowers in the different flowering stages were used to detect the scent compounds with the method of head space solid phase microextraction(HS-SPME) and gas chromatography/mass spectrometer (GC/MS); the detailed information was stated and the results presented in our previous work [15,30]. Altogether, 21 different samples were subjected to Illumina RNA-seq analysis [15].…”
Section: Plant Materials and Transcriptome Sequencingmentioning
confidence: 99%
“…Fresh flowers in the different flowering stages were used to detect the scent compounds with the method of head space solid phase microextraction(HS-SPME) and gas chromatography/mass spectrometer (GC/MS); the detailed information was stated and the results presented in our previous work [15,30]. Altogether, 21 different samples were subjected to Illumina RNA-seq analysis [15]. Reads per kilobase of exon per million reads mapped (RPKM) values were measured to the transcript abundance of each gene.…”
Section: Plant Materials and Transcriptome Sequencingmentioning
confidence: 99%
See 1 more Smart Citation
“…(Oleaceae), usually known as Baoxing osmanthus, is one of the rare spring flowering endemic Osmanthus species of which narrowly and sporadically distributed under the evergreen broad-leaved forests at elevations of 1800-2400 m in west Sichuan Province, China (Xiang and Liu 2008). Although it occupies an important phylogenetic node in genus Osmanthus, and plays a crucial germplasm resource for genetic breeding of sweet osmanthus, the genetic information of O. serrulatus is still limited so far (Chen et al 2015), while most study always focus on O. fragrans (Mu et al 2014;Yang et al 2018;Duan et al 2019). So, it is necessary to develop genetic resources of O. serrulatus to provide basic intragenic information for the further study on phylogeny and biogeography in genus Osmanthus.…”
mentioning
confidence: 99%